2010
DOI: 10.1007/s11302-010-9188-5
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine amine congener mitigates noise-induced cochlear injury

Abstract: Hearing loss from noise exposure is a leading occupational disease, with up to 5% of the population at risk world-wide. Here, we present a novel purine-based pharmacological intervention that can ameliorate noiseinduced cochlear injury. Wistar rats were exposed to narrow-band noise (8-12 kHz, 110 dB SPL, 2-24 h) to induce cochlear damage and permanent hearing loss. The selective adenosine A 1 receptor agonist, adenosine amine congener (ADAC), was administered intraperitoneally (100 µg/kg/day) at time intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…N 6 -[4-[[[4-[[[(2-Aminoethyl)amino]carbonyl]methyl]anilino]carbonyl]methyl]phenyl]adenosine ( 46 , ADAC) is a potent A 1 AR agonist that has been shown to be neuroprotective in various models. 6,30 Full agonist 10 displayed efficacy in a seizure model in mice without the toxicity observed in the active dose range (tested up to 30 mg/kg, i.p.). Other A 1 AR agonists began to show toxicity, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…N 6 -[4-[[[4-[[[(2-Aminoethyl)amino]carbonyl]methyl]anilino]carbonyl]methyl]phenyl]adenosine ( 46 , ADAC) is a potent A 1 AR agonist that has been shown to be neuroprotective in various models. 6,30 Full agonist 10 displayed efficacy in a seizure model in mice without the toxicity observed in the active dose range (tested up to 30 mg/kg, i.p.). Other A 1 AR agonists began to show toxicity, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In the cochlear partition, perfusion of adenosine in either perilymph or endolymph showed no changes in cochlear physiological parameters such as CAP [23,25] and no in vitro study has been published. However, Vlajkovic et al [42] (this issue; see also [43]) provides evidence that A1 receptor activation facilitates recovery from noise-induced hearing loss. In addition, prophylactic treatment with P1 receptor agonists confers otoprotection from noise damage [44,45].…”
Section: P1 Receptors In the Inner Earmentioning
confidence: 99%
“…The absence of ADK in the inner hair cells and Deiters' cells in the adult cochlea suggests reduced adenosine removal from the local pericellular spaces and enhanced adenosine signalling via adenosine receptors abundantly expressed in these cells (Vlajkovic et al,2007). Stimulation of A 1 receptors may be crucial for the survival of these cells under stress (Vlajkovic et al,2010; Wong et al,2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, R ‐PIA and 2‐chloro‐N6‐cyclopentyladenosine (CCPA) reduce cisplatin‐induced auditory threshold shifts (Whithworth et al,2004), most likely by promoting the antioxidant defense system (Ford et al,1997a). More recent studies (Wong et al,2010; Vlajkovic et al,2010) have demonstrated that adenosine and the selective A 1 adenosine receptor agonists CCPA and adenosine amine congener (ADAC) ameliorate cochlear injury and reverse hearing loss after exposure to traumatic noise. Further studies are thus warranted to determine the full potential of adenosine signalling in mitigating cochlear pathologies based on oxidative stress.…”
mentioning
confidence: 99%